Follicular dynamics and production of oocytes in young Nellore heifers with energetic supplementation - Nogueira, Ériklis; Silva, Ailson Sebastião da; Amaral, Thaís Basso; Ítavo, Luís Carlos Vinhas; Dias, Alexandre Menezes; Mingoti, Gisele Zoccal [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
To verify the effects of energy supplementation and fat on follicular dynamics, metabolic profile and the production of oocytes, 15 young heifers (Bos taurus indicus) with an average age of 14 months and with an initial weight of 256.35 kg were assigned to two treatments according to weight and follicular population as evaluated by ultrasonography: in T1 (1.0 × M), animals received 100% of the energy requirements for maintenance; in T2 (1.7 × M), animals received 170% of the energy requirements for maintenance, achieved by the addition of 200 g of Megalac®. After a period of adaptation to the diet, the treatments, blood collection and follicular aspirations were started using a randomized design. The dry matter intake and weight gain were lower in the 1.0 × M group than in the 1.7 × M group. No differences were found in the plasma progesterone concentrations, albumin, glucose, urea or gonadotropin (FSH and LH) levels between the groups. The mean concentrations of cholesterol were higher in the 1.7 × M group. The total number of small (<4 mm) and medium follicles (4-8 mm) was not altered by the treatments, but the number of small follicles increased on days 1 and 2 of the estrous cycle, with higher values found in the 1.7 × M group. The average of the oocytes also increased (9.50±2.1 and 12.5±4.4 for the 1.0 × M and 1.7 × M groups, respectively). The rapid increase in the amount of energy offered in the diet changes the amount of follicles and oocytes available for follicular aspiration (OPU) in young heifers without changing their metabolic profile.
Keywords: metabolic profile; nutrition and reproduction; OPU